Teachers’ And Students’ Attitudes Towards Integrating Environmental Education in the Secondary School Curriculum for Managing Environmental Degradation in Machakos Sub County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2018)
This study investigated implementation of integrated environmental education in the secondary school curriculum for managing environmental degradation in Machakos Sub-County. The study was thus informed by Fullan’s theory of educational change (2007). The theory views the implementation of IEE programme through lenses of four independent variables identified as need; clarity; complexity; quality and practicality on the one hand and teachers’ and students’ levels of environmental awareness, knowledge, skills, attitudes and participation as dependent variables on the other hand. These variables network with local factors and external factors as intervening variables to determine the IEE implementation process. The study employed cross-section survey design under the quantitative approach. Probability sampling designs were used to select participants for the study. The target population of this study was public secondary schools, teachers and form 4 students from Machakos Sub-County. Stratified and simple random sampling techniques were employed in sampling secondary schools, teachers and students. Questionnaires were used for data collection. Quantitative data were analysed using simple descriptive statistics. Overall study findings demonstrated that both teachers’ and students’ attitudes towards integrated environmental education in the secondary school curriculum were fairly positive though not adequate enough for effective implementation of IEE in the school curriculum hence, the unyielding environmental degradation in Machakos Sub-County. The study recommended that The Ministry of Education and the relevant urgencies such as KICD, DQAS and KNEC work jointly with school managers to draw an action plan to reinforce and intensify teachers’ and students’ levels of environmental attitudes through pre-service and in-service training, workshops and seminars on contemporary environmental issues. It is also recommended that studies are undertaken to understand those impediments that impede change in teachers’ and students’ environmental attitudes so that useful and practical interventions can be identified.